Olav Stokke (ed.), Aid and Political Conditionality, EADI Book Series 16, London: Frank Cass, 1995,4175.; Peter Gibbon (ed.), Markets, Civil Society and Democracy in Kenya, Uppsala: Nordiska Afrikainstitutet, 1995, 179 s. - Elklit, Jørgen (Politica, 1996)
-